Behaviors Associated With a Risk of HIV Transmission From HIV-Positive Street Youth to Non–Street Youth in Ukraine. Issue 9 (September 2015) - Nerlander, Lina M.C.; Zapata, Lauren B.; Yorick, Roman; Skipalska, Halyna; Smith, Ruben A.; Kissin, Dmitry M.; Jamieson, Denise J.; Vitek, Charles R.; Hillis, Susan D.
Abstract : Background: Little is known about the extent to which HIV-infected street youth (living part or full time on the streets) exhibit behaviors associated with HIV transmission in their interactions with youth not living on the streets ("non–street youth"). We aimed to determine prevalences and predictors of such "bridging behaviors": inconsistent condom use and needle sharing between HIV-positive street youth and non–street youth. Methods: A total of 171 street youth in 3 Ukrainian cites were identified as HIV infected after testing of eligible participants aged 15 to 24 years after random selection of venues. Using data from these youth, we calculated prevalence estimates of bridging behaviors and assessed predictors using logistic regression. Results: Overall, two-thirds of HIV-infected street youth exhibited bridging behaviors; subgroups with high prevalences of bridging included females (78.3%) and those involved in transactional sex (84.2%). In multivariable analysis, inconsistent condom use with non–street youth was associated with being female (adjusted prevalence ratio [aPR], 1.2; 95% confidence interval [CI], 1.1–1.4), working (aPR, 1.2; 95% CI, 1.03–1.4), multiple partners (aPR, 1.4; 95% CI, 1.2–1.6), and "never" (aPR, 1.4; 95% CI, 1.1–1.6) or "sometimes" (aPR, 1.3; 95% CI, 1.02–1.8) versus "always" sleeping on the street. Needle sharing with non–street youth was associated with being male (aPR, 1.4; 95% CI, 1.02–2.0), orphaned (aPR, 2.3; 95% CI, 1.8–3.0), and 2 years or less living on the streets (aPR, 1.8; 95% CI, 1.5–2.1). Conclusions: Bridging behaviors between HIV-infected street youth and non–street youth are common. Addressing the comprehensive needs of street and other at-risk youth is a critical prevention strategy. Abstract : Among HIV-positive street youth in Ukraine, more than two-thirds engage in behaviors such as needle sharing or inconsistent condom use that put non–street youth at risk for HIV infection.